2013
DOI: 10.1128/aac.01822-12
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic-Pharmacodynamic Modeling of Unboosted Atazanavir in a Cohort of Stable HIV-Infected Patients

Abstract: Limited data on the pharmacokinetics and pharmacodynamics (PK/PD) of unboosted atazanavir (uATV) in treatment-experienced patients are available. The aim of this work was to study the PK/PD of unboosted atazanavir in a cohort of HIV-infected patients. Data were available for 58 HIV-infected patients (69 uATV-based regimens). Atazanavir concentrations were analyzed by using a population approach, and the relationship between atazanavir PK and clinical outcome was examined using logistic regression. The final PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…It was suggested that an unboosted ATV daily dose of 900 mg would be required for subjects >13 years old and 475 mg for subjects 6–13 years old. Our data support the need for a much higher dose than is currently recommended as both the ATV 400 and 600 mg dose in our study produced exposures in adolescents and young adults below those achieved with ATV/r that achieve a good virologic response in adults (9). The impact of higher unboosted doses on the virologic efficacy in this heavily treated group is difficult to extrapolate but the safety data reported with higher ATV exposure in these children and adolescents are reassuring (6).…”
Section: Discussionsupporting
confidence: 82%
“…It was suggested that an unboosted ATV daily dose of 900 mg would be required for subjects >13 years old and 475 mg for subjects 6–13 years old. Our data support the need for a much higher dose than is currently recommended as both the ATV 400 and 600 mg dose in our study produced exposures in adolescents and young adults below those achieved with ATV/r that achieve a good virologic response in adults (9). The impact of higher unboosted doses on the virologic efficacy in this heavily treated group is difficult to extrapolate but the safety data reported with higher ATV exposure in these children and adolescents are reassuring (6).…”
Section: Discussionsupporting
confidence: 82%
“…ATV shows an EC 50 of 2-5 nM range against HIV-1 group M subtypes (A-D, AE, AG, F, G, and J) in in vitro system. A population pharmacokinetic model, including a mixed model of absorption, suggested a significant difference in ATV pharmacokinetics, regimens, and virological failure between the patients experiencing unboosted ATV [42]. Accordingly, recommended dosing of ATV is 300 mg with RTV, a PI booster with food or only ATV 400 mg once daily with food.…”
Section: Weak Cyp Inhibitorsmentioning
confidence: 99%
“…Further studies, in which food intake is controlled for, should be performed to determine the causes of high interindividual variability in ATV absorption. Reducing unexplained interindividual variability in predictive models could be of great help in clinical settings, especially considering the recent results reported by Goutelle et al , indicating that patients treated with ATV showing virological failure had lower k a values than those without failure.…”
Section: Discussionmentioning
confidence: 99%